Occupational lung disease: A narrative review of lung conditions from the workplace - Mohd Iskandar Jumat; Firdaus Hayati; Syed Sharizman Syed Abdul Rahim; Sahipudin Saupin; Khamisah Awang Lukman; Mohammad Saffree Jeffree; Helen Benedict Lasimbang; Fairrul Kadir (Elsevier Ltd, 2021)
Occupational lung diseases are lung conditions caused or made worse by materials when a person is exposed to a workplace. The diagnosis of an occupational disease is important for workers’ decision to continue work and for their eligibility under compensation programmes. We revisit the existing lung diseases that are closely associated with the occupation at the workplace namely occupational asthma, silicosis, black lung disease, farmers’ lung disease, asbestos-linked disease, and hypersensitivity pneumonitis. Occupational lung diseases contribute toward global health and economic impacts. Prevention and control of occupational lung diseases require a collaborative effort among employers, workers, occupational physicians, pulmonary physicians, industrial hygienists, and members from other disciplines.